Trends, impacts, and prospects for implementing artificial intelligence technologies in the energy industry: The implication of open innovation - Olesya Dudnik; Marina Vasiljeva; Nikolay Kuznetsov; Marina Podzorova; Irina Nikolaeva; Larisa Vatutina; Ekaterina Khomenko; Marina Ivleva (Journal of Open Innovation: Technology, Market, and Complexity, 2021)
This research aims to substantiate the impact of using open innovation (OI) in the energy sector in readiness to implement artificial intelligence (AI) technologies and their effectiveness. The empirical method was proposed to determine the readiness level of OI for the implementation of AI technologies by comparing Russian and French energy companies. Readiness level indicators of companies for AI implementation using the Fibonacci sequence, Student's t-test, and the method of fuzzy sets were empirically determined. The integrated readiness indicator for AI implementation by companies was calculated using the method of fuzzy sets and expressed through variance, allowing for these significant factors. Russian companies are at a low level of developmental readiness to implement AI, which is in contrast to companies operating in a developed market where the determining factor is the AI technology cost. The example of the innovative business model "Energyas- a-Service" shows the synergistic effects of OI use and AI technology introduction. This paper is novel because it seeks to contribute to the current debate in the literature, justifying the position that energy companies that have in the past actively applied the concept of open innovation in business, are the most competitive and most efficient in implementing AI technologies.
Keywords: 650; open innovation; artificial intelligence; energy industry; efficiency improvement